S60 Lung cancer surgical survival and volume in england. (15th November 2016) - West, D; Beckett, P; Khakwani, A; Hubbard, R; Dickinson, R; Woolhouse, I
Abstract : Introduction: The National Lung Cancer Audit has collected data for over 10 years demonstrating gradually rising resection rates in the UK. The Clinical (formerly Consultant) Outcomes Programme (COP) is an NHS England initiative, managed by HQIP, using national audit data to publish quality measures at the level of individual consultants. The lung cancer COP focusses on activity at individual surgeon level, and on survival at unit level. The first lung cancer COP in 2014 demonstrated overall 30 and 90-day survival of 97.8% and 95.5%. Methods: Data submitted to the NLCA for patients having curative-intent surgery who underwent surgery in 2013 was sent to the clinical lead at each surgical unit for validation and addition of responsible surgeon GMC number, with the option to add surgical cases if they were not included in the supplied dataset. Date of death was derived by a link to the Office of National Statistics. Units reporting unadjusted survival proportions more than three standard errors outside the national mean ("alarm" level) at 30 or 90 days were identified as statistical outliers. Results: All of the 28 surgical units in England participated in the audit, submitting a total of 4892 cases. Median annual unit activity was 156 resections (IQR 99–221, range 39–481). Median annual activity for individual surgeons was 39 (IQR 20–52, range 1–152). Overall 30-day survival was 98% and 90-day survival was 96%. There were no units with statistical outliers at the alarm level at 30-days and 90-days (see Figure ). Conclusion: Volume of activity varies widely by unit and individual surgeon. Survival after lung cancer surgery is very high, is improving, and is not statistically significantly different across the surgical units in England. This suggests that lung cancer teams may still be risk averse when considering surgical treatment of their patients. Reasons why patients die between 30 and 90 days is worthy of further investigation. Case-mix adjustment will be needed to allow robust comparisons between units.